Designation of Potential Excavation Zones Suitable for Mining - Modelling Different Types of Land Uses; MINATURA2020 Hungarian Case Study (Tállya Region) - Zoltán Horváth; Rita Szeiler; Anouk Cormont; Michiel van Eupen (Fábos Conference on Landscape and Greenway Planning, 2016)
The exploitation of minerals in Europe is an indispensable activity to ensure that the present and future needs of the European society can be met. This means that sufficient access is required to explore and exploit minerals. At the same time the mineral requirements of our society must be met without compromising the ability of future generations to meet their own needs. Accordingly, potentially exploitable mineral deposits (known deposits, abandoned mines and historical mining sites) need to be assessed against other land uses, taking into account criteria such as habitats, other environmental concerns, priorities for settlements, etc. Decisions on the development or management of these diverse land uses requires adequate consideration of their significance and the exclusiveness (MINATURA2020 press release 2015). A strategic national land-use planning policy for minerals requires reliable geological information on the known or potential deposits in order to safeguard resources and their environments from unnecessary sterilisation (ADWG 2014). A new EU project entitled MINATURA 2020 (www.minatura.eu) – Developing a concept for a European minerals deposit framework, funded within the European Commission’s Horizon 2020 Programme, was launched in the beginning of 2015 as a response to social needs to safeguard mineral deposits of public importance for the future. The exploitation of indigenous mineral deposits in Europe is essential if we are to ensure that the needs of European society can be satisfied in a sustainable manner.
Keywords: greenways; mining; excavation; land use; hungary; MINATURA2020